Motherhood and Home Quarantine: Exploring the Experiences of Iranian Mothers in Caring for their Children During the COVID-19 Outbreak - Anahita Khodabakhshi-koolaee; Mahsa Aghaei Malekabadi (Iran University of Medical Sciences, 2020)
Background: Following the spread of new coronavirus disease (COVID-2019) in Iran, people began a new lifestyle in quarantine to survive the disease. Mother-child relationships were affected by this new lifestyle. This phenomenological study was conducted to explore the experiences of Iranian mothers in caring for their children during COVID-19 outbreak. Methods: This qualitative study was conducted with an interpretive phenomenological approach. The participants were selected using purposive sampling among mothers living in Tehran in 2020. The data were collected through semi-structured interviews. The participants were mothers with 7- to 9-year-old children with the experience of living in quarantine.  The collected data were theoretically saturated after 17 interviews. All the interviews were recorded and transcribed, and the resulting data were analyzed using van Manen's phenomenological approach. Results: Four main themes were extracted from the collected data: the mother's health and physical concerns, confusion in playing the motherhood role, concerns about educational quality and wasting learning opportunities, and concerns about the impact of financial disputes on children.  Conclusion: The experiences of the mothers as the main caregivers in home quarantine were very unique. Understanding the complexities of their experiences, beliefs, and attitudes about motherhood and caring for children in quarantine can provide useful insights for decision-makers, healthcare professionals, and mental health professionals.